EKSPEKTASI PROFETIK UMAT KRISTEN DI ERA DIGITAL: REINTERPRETASI ESKATOLOGI DALAM BUDAYA MEDIA SOSIAL - Yonatan Alex Arifianto (Sekolah Tinggi Teologi Arastamar Bengkulu, 2026)
The rise of social media has fundamentally transformed the way the Christian faith is expressed and understood in the public sphere of our time. Christian eschatology and prophetic expectations have undergone a shift in meaning due to the digital logic that emphasises speed, visualisation, and the virality of religious narratives. Consequently, prophetic language, which should shape the hope of faith, is often reduced to sensationalist discourse lacking theological reflection and pastoral discernment. This study aims to reframe Christian eschatology theologically and critically so that it remains relevant and responsible within social media culture. Using a qualitative method with a literature review and theological analysis, it can be concluded that Christian eschatology in both classical and contemporary traditions demonstrates that prophetic expectations are theologically rooted in eschatological hope, which shapes the faith and life orientation of believers. However, within the context of social media as a space for theological mediation, prophetic language undergoes a transformation that often shifts hope into religious sensationalism, which has the potential to weaken the depth of faith reflection. Therefore, a reframing of Christian eschatology is required through theological discernment and pastoral responsibility so that prophetic expectations remain faithful to the Christian faith and biblical values